Disaster Communication Campaign Via Instagram and Twitter Palang Merah Indonesia - Nur Muliasari; Vinka Audrina Sahrir; Nursaleh Hartaman (Universitas Muhammdiyah Yogyakarta, 2022)
This study aimed to find out the effect given by the campaign with determining the effect of